The Influence of Content Marketing, Influencer Marketing and Electronic Word of Mouth on Consumer Loyalty of Kanzler Products in Tiktok Platform - Nadila Ayu Citra Armana; Indah Respati Kusumasari (Yayasan Riset dan Pengembangan Intelektual, 2024)
Social media is currently the most crucial platform for entrepreneurs trying to sell their goods. Many firms, like PT Macroprima Panganutama, are embracing influencer and content marketing as techniques to draw buyers to their products because of the popularity of social media and the ease with which people can use the Internet. Additionally, entrepreneurs can simply disseminate information about their goods and services through a range of media, including text, photos, and videos—basically, electronic word-of-mouth marketing. Through tiktok platforms, this study investigates the effects of electronic word-of-mouth, influencer marketing, and content marketing on consumer loyalty to Kanzler products in Surabaya. The purpose of this research is to investigate the potential impact of content marketing, influencer marketing, and electronic word of mouth on consumer loyalty. With a sample size of 100 respondents, purposive sampling was used to obtain sampling. This research uses a quantitative methodology using multiple linear regression analysis to handle data collected through distributing questionnaires. The research result indicate that while influencer marketing has a positive and significant impact on consumer loyalty, content marketing has a positive and significant impact on consumer loyalty, and electronic word of mouth has no impact on consumer loyalty.